Peran Influencer Media Social Dalam Impulsive Buying dan Konsumsi Generasi Z : Studi Kasus Marketplace Shopee - Khoirun Nisa; Qoni'ah Nur Wijayani (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2024)
Abstact This research aims to examine the role of social media influencers in Generation Z's impulse buying and consumption, focusing on a case study on the Shopee marketplace platform. Generation Z is a significant consumer group in today's digital economy, and social media has become one of the main channels to influence their shopping behavior. The research method used is a qualitative approach, which includes social media content analysis, generation Z interviews, and a survey to generation Z who shop at Shopee. The results of this study reveal that social media influencers have a significant role in influencing generation Z's impulse buying decisions on Shopee. They are able to create a strong shopping impulse through engaging and persuasive content.